Peran Pemerintah dalam Pelayanan Pendidikan melalui Sarana Prasarana Madrasah di Kantor Wilayah Kementerian Agama Provinsi Jawa Timur - Salam, Abdul; Pramudiana, Ika Devy (Soetomo Magister Ilmu Administrasi, 2025)
The Regional Office of the Ministry of Religion of East Java Province has made various efforts to improve the public service system, especially education services, by increasing access and quality of madrasa facilities and infrastructure quickly and transparently, to overcome current problems with madrasa facilities which have an impact on access to education services, especially madrasa facilities and infrastructure. . This research aims to describe and analyze the role of the Government in educational services for Madrasah facilities and infrastructure in the Regional Office of the Ministry of Religion, East Java Province, Analyze the factors that hinder and support the role of the Government in educational services for Madrasah facilities and infrastructure in the Regional Office of the Ministry of Religion, East Java Province and Identifying the most dominant benefits of the Government’s role in educational services for Madrasah facilities and infrastructure at the Regional Office of the Ministry of Religion, East Java Province. The method used in this research is a qualitative descriptive method. The data sources used are primary and secondary data sources related to the empirical situation and conditions of the government’s role. In this research, the author used interview research to obtain primary and secondary data as well as other supporting data. The results of the research show that in the process of reviewing the government’s role in educational services, madrasa facilities and infrastructure at the Regional Office of the Ministry of Religion, East Java Province obtained a basic reference for regulations on facilities and infrastructure in educational services based on the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 22 of the Year 2023 regarding facilities and infrastructure. Continuous human resource facilities and guidance are proven by the availability of online applications, namely SIM-SARPRAS and SIMPRO SBSN. The last one is right on target in the distribution of programs and assistance for madrasa facilities and infrastructure through priority development from the Regional Office of the Ministry of Religion of East Java Province. Supporting factors in the government’s role are as a regulator, dynamist, facilitator and catalyst as well as providing guidance to madrasas. The inhibiting factors found were socio-economic conditions and resources. In the end, the government should maximize the distribution of programs and aid in a targeted manner. Apart from that, it is necessary to improve madrasah human resources regarding the importance of managing madrasah facilities and infrastructure.